Risks of Foreign Economic Activities in Tourism: Consideration In Income Accounting - Vysochan, Oleh; Defir, Ihor; Vysochan, Olha; Hyk, Vasyl; Lytvynenko, Nataliia; Olshanska, Mariia (International Journal of Accounting and Economics Studies, 2025)
Reducing risks associated with tourism activities is one of the key tasks for tour operators and travel agencies. The article is devoted to solving the problems of identifying risks of tourism enterprises when recognizing and accounting for revenue at each stage of the company’s sales cycle. The methodology is based on the provisions of accounting and reporting standards, both national and international, as well as the specific characteristics of the travel company’s economic activity. The result of using the date of completion of the tour to establish the moment of recognition of revenue from the sale of a travel product by a travel agent and the combined method of revenue recognition, based on the degree of completion of the transaction for the provision of services at the reporting date, is to ensure compliance with the principle of prudence in the accounting of travel companies, to establish the optimal ratio between the reliability of the array of information on revenue received and the degree of risk to ensure the investment attractiveness of the company.